Functional properties of films based on soy protein isolate and gelatin processed by compression molding - Guerrero, P. (2011)
Soy protein isolate (SPI) based films, blended with gelatin and plasticized with glycerol at pH 10, were prepared by compression molding with the aim to obtain environmentally friendly materials for packaging applications. Different contents and types of gelatin were incorporated into SPI-based mixtures to improve mechanical properties. All films obtained were flexible and transparent. Films with 15% of bovine gelatin showed higher tensile strength and similar elongation at break compared with the ones without gelatin. Moreover, contact angle measurements showed that the addition of gelatin decreased the hidrophilicity of the films, while UV barrier properties were maintained. The effect of gelatin addition has been explained using Fourier transform infrared (FTIR) and the changes observed in the intensity of the bands corresponding to the amide group showed that gelatin interacts with SPI, which was confirmed by the decrease of total soluble matter.